Nanosuspension: An Emerging Trend for Bioavailability Enhancement of Etodolac - Samar A. Afifi; Maha A. Hassan; Ali S. Abdelhameed; Kadria A. Elkhodairy (International Journal of Polymer Science)
Etodolac (ET) (poorly soluble drug) nanosuspensions were prepared by both pH shift method and antisolvent techniques in order to increase its dissolution rate. Various stabilizers were used, namely, Tween 20 and 80, HPMC, PVP K44, PVA, PEG 400, NaCMC, and β-cyclodextrin. The prepared nanosuspensions were characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) and evaluated for their particle size, particle size distribution, and in vitro dissolution rate. In general, it was found that the antisolvent method for the preparation of ET nanosuspensions reduced the drug particle size to a higher extent compared to the pH shift method. The dissolution rate of ET in distilled water was markedly enhanced in the nanosized system, as more than 65% of drug dissolved in 10 min from all the nanosuspension formulations except F5 (stabilized with PVP K44) and F8 (stabilized with Tween 20), as compared to less than 20% of crude drug. Nanoparticles prepared by antisolvent method using Tween 80 as a stabilizer were selected for further in vivo study. The in vivo test demonstrated that nanoparticles of ET were well absorbed with a percentage drug absorption value 2.7 times more than that of micrometric size of crude ET.